Robust Contract Conditions Under the Newly Introduced BTO-rs Scheme: Application to an Urban Railway Project - Kangsoo Kim (KDI Journal of Economic Policy, 2020)
Few studies have specifically focused on the uncertainty of demand forecasting despite the fact that uncertainty is the one of greatest risks for governments and private partners in PPP projects. This study presents a methodology for finding robust contract conditions considering uncertainty in travel demand forecasting in a PPP project. Through a case study of an urban railway PPP project in Korea, this study uncovered the risk of excessive government payments to private partners due to the uncertainty in contracted forecast ridership levels. The results allow the suggestion that robust contract conditions could reduce the expected total level of government payments and lower user fees while maintaining profitability of the project. This study offers a framework that assists contract negotiators and gives them more information regarding financial risks and vulnerabilities and helps them to quantify the likelihood of these vulnerabilities coming into play during PPP projects.
Keywords: R42; R40; 330; PPP; BTO-rs; Contract Conditions; Robustness; Uncertainty; Forecast; Ridership